Enhancing Financial Literacy at St. Louis 1 Senior High: Universitas Ciputra Financial Club's Commitment to Student Investment Education - Wendra Hartono; Kartikasari Gunawan; Aria Ganna Henryanto; Kimberly Valencia; Gilbert Hutomo Konrad; Johanes Marco Poilot; Meyer Chang; Calvin Stefanus; Richelle Jesslyn; Yuli Kartika Dewi; Laij Victor Effendi (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
In this growing era, an individual's investment skills are not only used in the scope of work, but also include long-term opportunities. Investment is one of the important instruments currently used as a financial strategy. Fraudulent investments have sprung up with various motives that make people afraid to invest. Now investment is gaining popularity among Generation Z, therefore the ability to invest must be developed and trained. This community service was held to improve investment skills by using fundamental analysis for St. Mary's High School students. The program was held on March 20, 27, 2024 and April 3, 2024. Several games and training seminars for St. Louis 1 related to